2019
DOI: 10.1128/aac.00426-19
|View full text |Cite
|
Sign up to set email alerts
|

Shortening Buruli Ulcer Treatment with Combination Therapy Targeting the Respiratory Chain and Exploiting Mycobacterium ulcerans Gene Decay

Abstract: Buruli ulcer is treatable with antibiotics. An 8-week course of rifampin (RIF) and either streptomycin (STR) or clarithromycin (CLR) cures over 90% of patients. However, STR requires injections and may be toxic, and CLR shares an adverse drug-drug interaction with RIF and may be poorly tolerated. Studies in a mouse footpad infection model showed that increasing the dose of RIF or using the long-acting rifamycin rifapentine (RPT), in combination with clofazimine (CFZ), a relatively well-tolerated antibiotic, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 39 publications
(39 reference statements)
1
50
0
Order By: Relevance
“…We therefore used a higher dose (1 mg/kg) that, still, failed to control infection in our model. Same unfavorable result was obtained with selamectine used at a dose of 12mg/kg as proposed in previous publication [19]. However, it has been suggested that these two avermectin compounds might be used safely at higher doses [12], which could be evaluated in future studies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We therefore used a higher dose (1 mg/kg) that, still, failed to control infection in our model. Same unfavorable result was obtained with selamectine used at a dose of 12mg/kg as proposed in previous publication [19]. However, it has been suggested that these two avermectin compounds might be used safely at higher doses [12], which could be evaluated in future studies.…”
Section: Discussionsupporting
confidence: 63%
“…Triple combinations of Q203, administered at the higher dose of 10 mg/kg, either with RPT and clofazimine, RPT and BDQ or BDQ and clofazimine, as well as quadruple combination of these four drugs, were recently found to be sterilizing after 2 weeks of daily treatment in BU animal model [19], leading to the conclusion that targeting the M. ulcerans respiratory chain with several drugs is an efficient strategy for designing new shorter treatments of BU. In the present study, we demonstrated that double combinations of Q203 at 5 mg/kg with either RPT or BDQ, thanks to the long half-life and good bio availabilities of these drugs, provided very promising results for future fully oral intermittent regimens which would greatly simplify BU treatments in the field.…”
Section: Discussionmentioning
confidence: 99%
“…As an extremely potent inhibitor of M. ulcerans respiration, Q203 is an exceptional candidate for treatment-shortening regimens. Recently, we described 3-drug combinations of drugs active on the ETC with and without rifapentine that appeared capable of shortening the treatment of BU (16). Q203-containing regimens proved to be most effective and cured all mice after treatment for just 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike Mycobacterium tuberculosis , classical strains of M. ulcerans have a naturally occurring mutation in the cydA gene that renders the cytochrome bd oxidase non-functional (15). Therefore, most M. ulcerans strains causing BU are exquisitely susceptible to Q203 with very low MICs of 0.000075-0.00015 µg/ml (16, 17). In vivo studies also show Q203 to be a very attractive candidate for treatment of BU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation